2015
DOI: 10.1039/c4ra15863f
|View full text |Cite
|
Sign up to set email alerts
|

A combined iron and thyroid hormone protocol suppresses ischemia–reperfusion injury in rat livers

Abstract: Liver preconditioning (PC) against ischemia–reperfusion (IR) injury is attained by iron (Fe) or thyroid hormone (T3) administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…PCA (Figure S6B, Supporting Information), Spearman analysis (Figure S6C, Supporting Information) and heat map (Figure S6D, Supporting Information) suggested that compared to the group receiving oral L‐T 4 treatment (L‐T 4 mice), the organs, particularly the hearts and livers of ST mice, exhibited a functioning state closer to that of normal animals (N mice). We examined the expression of important T 3 ‐regulated genes ( THRSP1 , [ 35 ] Dio1 , [ 36 ] ME1 , [ 37 ] and Myh6 [ 38 ] ), as well as genes associated with T 3 malfunctions, ( Per3 [ 39 ] and Ciart [ 40 ] related to circadian rhythm, Trib3 [ 41 ] related to glucose regulation, Gclc [ 42 ] related to glutathione synthesis, Cyp2c69 and Cyp21a1 related to lipid metabolism, [ 43 ] Esm1 and Aplnr [ 44 ] related to angiogenesis) using qRT‐PCR (Figure S7A, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…PCA (Figure S6B, Supporting Information), Spearman analysis (Figure S6C, Supporting Information) and heat map (Figure S6D, Supporting Information) suggested that compared to the group receiving oral L‐T 4 treatment (L‐T 4 mice), the organs, particularly the hearts and livers of ST mice, exhibited a functioning state closer to that of normal animals (N mice). We examined the expression of important T 3 ‐regulated genes ( THRSP1 , [ 35 ] Dio1 , [ 36 ] ME1 , [ 37 ] and Myh6 [ 38 ] ), as well as genes associated with T 3 malfunctions, ( Per3 [ 39 ] and Ciart [ 40 ] related to circadian rhythm, Trib3 [ 41 ] related to glucose regulation, Gclc [ 42 ] related to glutathione synthesis, Cyp2c69 and Cyp21a1 related to lipid metabolism, [ 43 ] Esm1 and Aplnr [ 44 ] related to angiogenesis) using qRT‐PCR (Figure S7A, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%